The effect of cadence on hip, knee and ankle contribution during cycling exercise - Skovereng, K.; van Beekvelt, M.; Ettema, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: During cycling, power is produced mainly by muscles spanning the hip knee and ankle joint and is transferred to the pedals. Both work rate and cadence have been shown to affect efficiency during cycling (Ettema and Lorås 2009) and is also thought to influence technical variables. Increasing hip joint contribution has been show with increasing work rate (Elmer et al 2011), but the effect of cadence has been investigated to a far lesser extent. Accordingly, the purpose of the present study was to investigate the effect of cadence on the hip, knee and ankle joint contribution during cycling exercise. Methods: 27 male recreational cyclists (VO2peak 53.0 ± 5.6 ml/kg/min) participated in the study. The participants cycled at approximately 75% the workload corresponding to the onset of blood lactate accumulation. All subjects cycled six four-minute stages at 60, 70, 80, 90, 100 and 110 rpm. The joint power contribution was calculated using inverse dynamics for measured pedal forces and kinematics. Results Hip joint percentage contribution decreased significantly as cadence increased from 42.8 ± 6.8 % at 60 rpm to 18.1 ± 7.8 % at 110 rpm. Correspondingly knee joint contribution increased from 44.9 ± 7.2 % at 60 rpm to 72.1 ± 7.4 % at 110 rpm. Ankle joint contribution decreased from 12.4 ± 3.9 % at 60 rpm to 9.8 ± 3.0 % at 110 rpm but the change was not significant. Discussion: The main finding of the present study was a decreasing contribution of the hip joint and increasing contribution from the knee joint in power production as cadence increased. The very clear differences in percentage joint contribution between hip and knee joint at different cadences indicate that there are distinct technical differences in cycling technique at different cadences. Elmer (2011) reported hip extension to be the most powerful action during high intensity cycling. Also Morniuex et al (2007) reported a larger hip contribution at high work rates. In accordance with these previous studies, our results indicate that low cadence at a medium intensity, have a larger hip contribution and thus resemble more the action at high intensity.